Unraveling the Truth: Investigating the Spread of Fake News on Facebook During the COVID-19 Crisis - Palomino-Flores, Paola (2024)
The COVID-19 pandemic has exposed global challenges in effectively communicating and preventing the spread of emergencies, amplified by the proliferation of fake news. Verification platforms played a crucial role in combating false information during the initial months of the outbreak. This study analyzes fake news prevalence in Peru during the COVID-19 crisis, using data from 114 viral news items on Facebook via the Chequeado verifier website, of which 70 were identified as fake. This study employs a mixed-methods approach, incorporating scientific, analytical-synthetic, and statistical methods, along with interviews and surveys, to uncover Facebook's significant role in the dissemination of misinformation and confusion by ant vaccine groups. The research highlights the urgent need for a collaborative strategy to counteract misinformation, utilizing real-time AI algorithms for detection and providing journalists with reliable data.